The Role of Sharia Product Innovation in Strengthening Islamic Financial Stability - Muhammad Sheva Mauladi (ICO EDUSHA, 2024)
This study aims to analyze the role of Islamic finance product innovation in supporting Islamic financial stability, particularly through the development of competitive products that comply with sharia principles. Islamic finance is based on the principle of prohibition against usury, gharar, and maisir, which encourages the creation of fair and transparent financial products. However, in the face of global market competition, innovation is needed so that Islamic financial products can meet the needs of modern society. This study found that innovations such as sukuk and Islamic fintech play an important role in expanding access to Islamic financial services, improving operational efficiency, and strengthening public trust. In addition, the management of social funds such as zakat through Islamic financial institutions can improve social welfare and empower the community's economy. In the rural context, the implementation of Islamic finance in Village-Owned Enterprises (BUMDes) also contributes to sustainable local economic growth. With the support of conducive regulations and increased Islamic financial literacy, this innovation is expected to strengthen Islamic financial stability and have a positive impact on the national economy. Keywords: Innovation, Islamic Products, Islamic Financial Stability.